Octavia E. Butler - Canavan, Gerry (Modern masters of science fiction., 2016)
"Gerry Canavan offers a critical and holistic consideration of Butler's career. Drawing on Butler's personal papers, Canavan tracks the false starts, abandoned drafts, tireless rewrites, and real-life obstacles that fed Butler's frustrations and launched her triumphs. Canavan departs from other studies to approach Butler first and foremost as a science fiction writer working within, responding to, and reacting against the genre's particular canon. The result is an illuminating study of how an essential SF figure shaped themes, unconventional ideas, and an unflagging creative urge into brilliant works of fiction."--Publisher's description